Aspirin does not confer protection against major ischemic vascular events in patients diagnosed with rheumatoid arthritis - Chao Gao; Qiqi Hou; Hongxia Cao; Cangtuo Li; Xu Peng; Quanle Han; Shouling Wu; Kangbo Li (Journal of International Medical Research)
Objective Rheumatoid arthritis (RA) is a chronic systemic autoimmune disease characterized by inflammatory arthritis and extra-articular involvement. Patients with RA are at increased risk of developing cardiovascular diseases. This retrospective cohort study aimed to determine whether acetylsalicylic acid (aspirin [ASA]) protects against major ischemic vascular events in patients diagnosed with RA. Methods Patients with RA were recruited from a population of 118, 500 participants who were enrolled into the Kailuan Cohort Study between 2014 and 2016. Information regarding demographic characteristics, anthropometric measures, and medical histories were documented. Patients with RA who underwent ASA therapy were propensity score matched at a ratio of 1:4 with patients with RA who did not receive ASA. The risk of ischemic vascular events (myocardial infarction and ischemic stroke) was examined. The relationship between ASA therapy and major ischemic vascular events was analyzed by Cox proportional hazards regression. Results A total of 939 patients with RA were included (189 who received ASA and 750 who did not). During the 3.3-year follow-up, six and 35 major ischemic vascular events occurred in the ASA and non-ASA groups, respectively, with no significant between-group difference in the cumulative incidence of such events. Cox proportional hazards regression analysis showed that ASA therapy was not associated with major vascular ischemic events and its subtypes. Conclusions ASA did not confer protection against major ischemic vascular events in patients diagnosed with RA.